Freight Transport for Development Toolkit : Ports and Waterborne Freight - Kruk, C. Bert; Donner, Michel (World Bank, Washington, DC, 2017)
The estimate of the United Nations Conference on Trade and Development is that more than 80 percent or close to 8 million tons in 2007, of world freight is transported by sea. Most, if not all, freight transport moves from the producer to the consumer through logistic processes thereby passing a number of nodal points. As for waterborne transport, sea and river ports and terminals form these nodal points where freight is transferred from one mode to another. Chapter one provides data on world maritime transport and explains the different types of cargo that pass which are carried by the world merchant fleet and the cargoes they carry. It also is explained that the former general cargo type of vessels have evolved into vessel designs that have specifically been designed for different types of cargoes. Chapter two provides an extensive overview of the development of the container in terms of what containers are, how dedicated container vessels have developed as well as the impact of containers on logistic processes, including hinterland connections. Chapter three provides an overview of the world port in terms of numbers and classifies the largest ports in the world in terms of total cargoes, containers and dry bulk. Chapter four presents an overview of the indicators used in ports. Chapter five describes how ports around the world are owned and managed. First the major characteristics and functions of ports are described and possible ownership structures are explained. The chapter six not only describes the aspect of emissions, but also describes other forms of pollution sources of the sector, as these are noise, light, dust and soil and water pollution. As is explained in chapter seven, port work has gradually changed from pure physical work to processing control using dedicated and complicated equipment and automated systems. Similarly, the work of seafarers has changed. Chapter eight provides tools as to how cities can cope with this issue; in particular how former port areas can be and have been re-integrated in the city. Chapter nine presents a number of examples comparing rates that were charged in 2008 with those in the same period in 2009. Finally, chapter ten provides a comparison between the World Bank's transport business strategy paper 2008-2012 and the issues presented in this overview of ports and waterborne transport.